ANALISIS PENGARUH ETIKA BISNIS ISLAM TERHADAP TINGKAT KEPUASAN PELANGGAN TOKO KENCANA WANGI KARANGANYAR - Anwar Achmadi; Muhammad Tho’in; Agus Marimin (Jurnal Ilmiah Ekonomi Islam, 2026)
This study aims to examine the influence of Islamic business ethics dimensions (Shiddiq, Amanah, Tabligh, and Fathonah) on customer satisfaction at Kencana Wangi Store, Karanganyar. A quantitative approach was employed with the Slovin formula to determine 55 respondents from a population of 120 customers. Data were collected through a Likert scale 1-5 questionnaire and analyzed using multiple linear regression with SPSS. Results show that simultaneously all four dimensions significantly influence customer satisfaction (F = 35.111; Sig. 0.000; R² = 0.737). Partially, Amanah (t = 2.888; Sig. 0.006) and Fathonah (t = 3.940; Sig. 0.000) have a positive and significant effect, while Shiddiq (Sig. 0.340) and Tabligh (Sig. 0.374) are not significant. Fathonah is the most dominant variable with the highest Beta value of 0.503. These findings underscore the importance of developing staff competence and professionalism in enhancing Islamic values-based customer satisfaction.